Morphology and biology of Polydora species (Polychaeta: Spionidae) boring into oyster shells in South America, with the description of a new species - Radashevsky, Vasily I.; Lana, Paulo C.; Nalesso, Rosebel C. (Zootaxa, 2006)
Four Polydora species boring into oyster shells in South America are described based on museumand new material collected mainly in Brazil. These include P. cf. haswelli newly recorded for South America, P. ecuadoriana and P. rickettsi newly recorded for the Atlantic coast of South America, and a new species described from Brazil. Extension of the distribution of these oyster-associated species may have resulted from transportation of oysters to South America for aquaculture. In all species, females deposit eggs into capsules which are joined to each other in a string and attached to the inner wall of the burrow. In P. ecuadoriana, P. cf. haswelli and P. rickettsi, larvae develop inside the capsules until the 3-chaetiger stage and then are released into the water column where they feed and develop until the 16–18-chaetiger stage. Polydora carinhosa sp. nov. exhibits lecithotrophy; larvae develop inside the capsules until the 14-chaetiger stage, then hatch and settle after a short planktonic stage. Newly settled individuals of all species construct a small silty tube on the shell surface before boring into the shell. Polydora ecuadoriana forms mud blisters on the inner side of oyster shells. Heavy infestation by this species poses a threat to oyster aquaculture in Brazil.